Mathematics and computation in music : 6th International Conference, MCM 2017, Mexico City, Mexico, June 26-29, 2017, Proceedings /: 6th International Conference, MCM 2017, Mexico City, Mexico, June 26-29, 2017, Proceedings. (2017) - Unknown
No abstract available